2018
DOI: 10.1007/s00423-018-1686-x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of surgical strategies in perforated left colonic diverticulitis with generalized peritonitis

Abstract: This systematic review suggests similar rates of complications but higher rates of colonic restoration after primary anastomosis compared to Hartmann procedure in perforated diverticulitis with generalized peritonitis (Hinchey III and IV). Results in laparoscopic lavage for Hinchey III are not superior to primary resection. However, further studies with a careful interpretation of the meaning of re-interventions are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
1
11
0
2
Order By: Relevance
“…In the three studies, a total of 358 Hinchey III patients were included of whom 185 underwent laparoscopic lavage [122][123][124]. Several meta-analyses have been performed with somewhat different results [125][126][127][128][129][130][131][132][133]. There are several noncomparative cohorts showing that laparoscopic lavage is feasible in selected patients [134].…”
Section: Which Surgical Approach Is Appropriate In Patients With Purumentioning
confidence: 99%
“…In the three studies, a total of 358 Hinchey III patients were included of whom 185 underwent laparoscopic lavage [122][123][124]. Several meta-analyses have been performed with somewhat different results [125][126][127][128][129][130][131][132][133]. There are several noncomparative cohorts showing that laparoscopic lavage is feasible in selected patients [134].…”
Section: Which Surgical Approach Is Appropriate In Patients With Purumentioning
confidence: 99%
“…The results of RCTs showed a similar morbidity and mortality in short term follow-up and reduced length of stay in HP patients; the long term followup showed more definitive stomas, a worse quality of life and higher morbidity after stoma reversal. The meta-analysis of RCTs [48] showed no statistical differences in mortality or major morbidity between PRA and HP. Stoma reversal rate was higher in PRA compared to HP, and morbidity was lower in PRA patients.…”
Section: Reconstruction After Sigmoid Colectomymentioning
confidence: 85%
“…LPL was proposed in 1996 [45] with initial favorable results [46][47][48] encouraging its unselective use in perforated diverticulitis with peritonitis [49]. Three subsequent randomised controlled trials (RCTs) comparing LPL to sigmoidectomy obtained different results [50][51][52] Recent meta-analyses also reached different conclusions on the 30-day and 90-day reoperation risk, possibly due to methodological flaws [53][54][55][56][57][58][59][60]. Some findings are conclusive: resolution of sepsis and early morbidity and mortality rates after LPL are similar to those after sigmoidectomy, rates of abscesses and unplanned reoperations at index admission are higher after LPL, and total reoperation rate (including planned stoma closure), permanent stoma rate and costs [61][62][63] are lower after LPL than after resective surgery.…”
Section: Considerationsmentioning
confidence: 99%
“…RCTs comparing PRA with HP found no significant difference in mortality and overall morbidity after the index procedure, but all studies were prematurely terminated due to slow patient recruitment or for safety reasons [66][67][68]. Likewise, meta-analyses of experimental/observational studies and RCTs reported similar rates of major complications and postoperative mortality both for Hinchey III and IV disease [58,[69][70][71]. More recently, the LADIES trial found no significant differences in short-term outcome both in Hinchey III and IV patients, although this study also ended prematurely confirming the trial's vulnerability to discontinuation in the emergency setting, a feature that potentially leads to an overestimation of treatment benefits [72].…”
Section: Considerationsmentioning
confidence: 99%